Evaluación de la Incidencia de la Construcción de la Represa de Hidrosogamoso en el Comportamiento de la Evapotranspiración (2022)
At present, there is a general concern about climate change and the impact of the exploitation of natural resources on this issue. In Columbia the 68% of the energy supply is generated by hydroelectric plants (Montes, 2019), for the construction of these it is necessary to take advantage of masses of water in movement, showing alterations in the terrestrial and aquatic ecosystems, in that sense the execution and commissioning of hydroelectric plants is associated with the change and decrease in services ecosystems, deforestation, alterations of the hydrological cycle, among other factors (Osorio Rosado, 2021).